Waste bank to improve sanitation community awareness in Ceubrek Pirak Village, North Aceh - Nanda Savira Ersa; Maulana Ikhsan; Teuku Ilhami Surya Akbar; B. Baidhawi; Muhammad Sayuti; Herman Fithra (Universitas Muhammadiyah Malang, 2023)
Some of the problems due to mismanaged waste include the potential of disease caused by bad sanitation and the risk of flooding when waste is thrown away to waterways or rivers. Therefore, it is necessary to sort and manage waste in a good manner to prevent disaster. One of the efforts to foster culture and change people's mindsets can be done by establishing Unimal Waste Bank. The main objective this activity is to develop a system in managing waste, especially inorganic waste through Unimal Waste Bank. The Unimal Waste Bank program is carried out in Ceubrek Pirak village, North Aceh Province for 6 weeks from September to October 2021. It was performed in some stages: location observation, socialization, collecting waste, and selling it. Community awareness and understanding about waste and environmental management is performed before waste bank is develop. The results showed that Unimal Waste Bank is promising to develop in this area due to good community enthusiasm and awareness. Several benefits can be obtained from this activity, for instance they receive profit from selling inorganic waste to Unimal Waste Bank. Moreover, they also have a chance to receive rewards at the end of each month during this program. The waste bank is expected to run well and develop various services to improve people's welfare and quality of life.